An Updated Assessment of the Use of Bioactive Chemicals Derived From Plants in Treatment of Colon Cancer - Sawant Ganesh,; Suryawanshi Abhijeet,; Jadhav Prakash,; Velhal Atish,; Priyanka Shinde,; Redasani Vivekumar, (Asian Journal of Pharmaceutical Research and Development, 2025)
The third most common type of cancer brought on by dietary, environmental, and hereditary causes is colon cancer. It is generally established that plant-based substances can regress colon cancer in a variety of ways, including by slowing the growth of tumors, controlling the negative effects of chemotherapy and radiation therapy, and acting at the molecular level. Carnosic acid, oleanolic acid, rosmarinic acid, emodin, eugenol, anthricin, flavonoids, polyphenol compounds, caffeic acid, catechins, saponins, polysaccharides, triterpenoids, alkaloids, glycosides, phenols, quercetin, luteolin, kaempferol, and luteolin glycosides are just a few of the numerous bioactive phytochemicals found in medicinal plants. Through a variety of mechanisms, including the blockage of cell cycle checkpoints and the activation of initiator and executioner caspase, these bioactive chemicals can inhibit the proliferation of tumor cells. Because of its anti-inflammatory, antioxidant, and anti-cancer qualities, traditional medicines have been utilized to treat cancer all over the world. Thisall bioactive chemicals derived from plant are used in treatment of colon cancer "